The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1124/mol.105.014019
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of BCRP (ABCG2) in the Biliary Excretion of Pitavastatin

Abstract: Pitavastatin, a novel potent 3-hydroxymethylglutaryl coenzyme A reductase inhibitor, is distributed selectively to the liver and excreted into bile in unchanged form in rats. We reported previously that the hepatic uptake is mainly mediated by organic anion transporting polypeptide (OATP) 1B1, whereas the biliary excretion mechanism remains to be clarified. In the present study, we investigated the role of breast cancer resistance protein (BCRP) in the biliary excretion of pitavastatin. The ATP-dependent uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
188
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(199 citation statements)
references
References 30 publications
4
188
7
Order By: Relevance
“…[12][13][14] BCRP also belongs to the ABC efflux transporter superfamily 26 and is widely expressed in the small intestine, liver and placenta, influencing the absorption and disposition of a variety of substrates. 27,28 It is noteworthy that Petain et al reported that IM clearance in patients carrying the ABCG2 421C/A genotype was significantly lower than in those with the 421C/C genotype. 29 To investigate the role of pharmacogenetic variation in IM metabolism and efficacy, SNPs within important IM exposure genes (ABCB1 (MDR1), ABCC2 (MRP2), ABCG2 (BCRP), CYP3A5, SLC22A1 (OCT1) and SLCO1B3 (OATP1B3)) were analyzed in IM-treated CML patients.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] BCRP also belongs to the ABC efflux transporter superfamily 26 and is widely expressed in the small intestine, liver and placenta, influencing the absorption and disposition of a variety of substrates. 27,28 It is noteworthy that Petain et al reported that IM clearance in patients carrying the ABCG2 421C/A genotype was significantly lower than in those with the 421C/C genotype. 29 To investigate the role of pharmacogenetic variation in IM metabolism and efficacy, SNPs within important IM exposure genes (ABCB1 (MDR1), ABCC2 (MRP2), ABCG2 (BCRP), CYP3A5, SLC22A1 (OCT1) and SLCO1B3 (OATP1B3)) were analyzed in IM-treated CML patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, BCRP has been shown to transport sulfated bile salt conjugates such as taurolithocholate sulfate in vitro 35 and to be involved in the biliary excretion of drugs such as pitavastatin. 36 It might therefore be speculated that BCRP contributes to the hepatocellular excretion of bile salts and xenobiotics. Furthermore, the heterodimeric transporter ABCG5/ABCG8 (ABCG5 and ABCG8) has been identified as the apical transport system involved in the hepatobiliary excretion of plant sterols and cholesterol (reviewed by Klett and Patel 37 and Kosters et al 38 ).…”
Section: Hepatic Transport Systemsmentioning
confidence: 99%
“…34 Hepatobiliary excretion of statins is mediated by ABCC2 and ABCB1 as well as ABCG2 and ABCB11, all of which belong to a family of transporters known to interact with lipophilic xenobiotics. [35][36][37][38][39][40] Variations in these transporters could alter duration of hepatic exposure, and therefore exposure to sites of action and to metabolizing enzymes. Variation in ABCC2, likely the largest contributor to biliary excretion of statins, is known to exhibit variation; however, this has been poorly studied in the context of statin transport.…”
Section: 30mentioning
confidence: 99%